Development and psychometric testing of a questionnaire to assess Nurse's perception of risks during enteral nutrition - Ping Feng; Hui-Li Yang; Lan Xu; Omorogieva Ojo; Xiao-Yan Lu; Hai-Ying Zhang; Xiao-Hua Wang (BMC, 2021)
Abstract Background Enteral nutrition (EN) therapy is widely used in clinical practice to provide artificial nutrition to patients, while the incidence of adverse events are relatively highly. In the clinical setting, the occurrence of adverse events is associated with the nurse's risk perception. Thus, using tool to evaluate nurse's risk perception of enteral nutrition is necessary. Methods The draft questionnaire with 37-items was formed by comprehensive literature reviews and semi-structured in-depth interviews with 11 nurses. Two iterations of expert consultations were used to evaluate the content validity, and 4 items were deleted in this phrase. A 33-items questionnaire was used to survey 352 nurses from five tertiary hospitals in China from May to July 2019 with convenience sampling. Content validity, construct validity and known-groups validity were evaluated by content validity index (CVI), exploratory factor analysis, and the comparisons of the different EN risk perception levels of nurses at different working departments and different educational backgrounds, respectively. Reliability was tested by internal consistency, test-retest reliability, and split-half reliability. Results After the exploratory factor analysis, four items were excluded. Finally, the newly developed questionnaire included 29 items explaining 71.356% of the total variance. It consisted of three factors: Risks of operation (15 items); Risks of EN-related adverse events (11 items), and Risks of EN solution selection (3 items). The CVI of the questionnaire was 0.95 and the CVI of items ranged from 0.875-1.0. The results of known-groups validity showed that the nurses with different educational backgrounds had a statistically significant difference of EN risk perception (z = − 3.024, p = 0.002), whereas there was not significantly different between EN risk perception of nurses working in different departments (z = − 1.644, p = 0.100). The Cronbach's α, test-retest reliability, and split-half reliability of the questionnaire were 0.967, 0.818, and 0.815, respectively. Conclusions The newly developed questionnaire for assessing nurse's EN risk perception showed good reliability and validity. It can be used as a tool for nursing managers to assess Chinese nurses' EN risk perception ability, so as to help to reduce the occurrence of adverse events during EN implementation.